STUDENTS’ READING COMPREHENSION BY USING REDW STRATEGY (READ, EXAMINE, DECIDE, WRITE) AT SMPN 2 CAMPALAGIAN POLEWALI MANDAR - Aminah Aminah (Publikasi dan UKI Press UKI Toraja., 2022)
This research aimed to detect whether REDW strategy has effect to the students’ reading comprehension at the third grade of SMPN 2 Campalagian. The method which used in this research was pre-experiment with one class pre-test and post-test design at the third grade of SMPN 2 Campalagian. The sample were 29 students from the total population 174 students. The result of the research and discussion that obtained by the writer at SMPN 2 Campalagian that there was effect of using REDW strategy on students’ reading comprehension after comparing the result of pre-test and post-test by getting improvement 63%. The writer was able to apply Read, Examine, Decide, write strategy to make the teaching process effective and it also helped students improve their reading comprehension.